2019
DOI: 10.1016/j.jpainsymman.2018.09.018
|View full text |Cite
|
Sign up to set email alerts
|

Concordance Between Proxy Level of Care Preference and Advance Directives Among Nursing Home Residents With Advanced Dementia: A Cluster Randomized Clinical Trial

Abstract: Context: Care consistent with goals is the desired outcome of advance care planning (ACP). Objectives: To examine concordance between advance directives and proxy care preferences among nursing home residents with advanced dementia, and determine the impact of an ACP video on concordance. Methods: Data were from Educational Video to Improve Nursing home Care in End-stage dementia (EVINCE); a cluster randomized clinical trial conducted in 64 Boston-area facilities (32/arm) from 2013–2017. Participants inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 42 publications
(60 citation statements)
references
References 40 publications
2
57
1
Order By: Relevance
“…In the nursing home setting, we have shown that dementia-specific decision aids can improve communication and decision-making for family caregivers, enhance palliative care treatment plans, improve goal-concordant care, and reduce hospitalizations. 46,47,48,49,50 Ongoing clinical trials include primary palliative care interventions to improve decision-making about treatment for infection in advanced dementia (TRAIN-AD AG032982) in nursing homes and dementia palliative care delivered community-dwelling patients and their families (IN PEACE AG057733). Given the large population of persons with Alzheimer’s and related dementias, and the prolonged suffering associated with this condition, improvements in both specialty and primary palliative care are necessary to improve outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…In the nursing home setting, we have shown that dementia-specific decision aids can improve communication and decision-making for family caregivers, enhance palliative care treatment plans, improve goal-concordant care, and reduce hospitalizations. 46,47,48,49,50 Ongoing clinical trials include primary palliative care interventions to improve decision-making about treatment for infection in advanced dementia (TRAIN-AD AG032982) in nursing homes and dementia palliative care delivered community-dwelling patients and their families (IN PEACE AG057733). Given the large population of persons with Alzheimer’s and related dementias, and the prolonged suffering associated with this condition, improvements in both specialty and primary palliative care are necessary to improve outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Documentation of values and preferences AD completion, 116,122,123,127,159 documents or discussions, 17,80,120,125,127,130 Goal concordant care Via medical record review alone 62,89,96,99,128,161 or also surrogate report 91,131,132 80,121,162 spiritual well-being, 90 surrogate well-being, 123,132 symptom management, 80 peacefulness 89 10 0 (0)…”
Section: (78)mentioning
confidence: 99%
“…The studies originated from the United States (Ahronheim, Morrison, Morris, Baskin, & Meier, 2000; Catic et al, 2013; Cohen et al, 2019; Hanson et al, 2017; Hilgeman et al, 2014; Mitchell et al, 2018; Orsulic‐Jeras, Whitlatch, Szabo, Shelton, & Johnson, 2019; Reinhardt, Chichin, Posner, & Kassabian, 2014; Song et al, 2019) and the United Kingdom (Brazil et al, 2018; Sampson et al, 2011). The study designs were randomized controlled trials (Ahronheim et al, 2000; Brazil et al, 2018; Cohen et al, 2019; Hanson et al, 2017; Hilgeman et al, 2014; Mitchell et al, 2018; Reinhardt et al, 2014; Sampson et al, 2011) and pre‐ and post‐test with or without a control group (Catic et al, 2013; Orsulic‐Jeras et al, 2019; Song et al, 2019).…”
Section: Resultsmentioning
confidence: 99%